Associations between major chain fast-food outlet availability and change in body mass index: a longitudinal observational study of women from Victoria, Australia. Issue 10 (16th October 2017) - Lamb, Karen E; Thornton, Lukar E; Olstad, Dana Lee; Cerin, Ester; Ball, Kylie
Abstract : Objectives: The residential neighbourhood fast-food environment has the potential to lead to increased levels of obesity by providing opportunities for residents to consume energy-dense products. This longitudinal study aimed to examine whether change in body mass index (BMI) differed dependent on major chain fast-food outlet availability among women residing in disadvantaged neighbourhoods. Setting: Eighty disadvantaged neighbourhoods in Victoria, Australia. Participants: Sample of 882 women aged 18–46 years at baseline (wave I: 2007/2008) who remained at the same residential location at all three waves (wave II: 2010/2011; wave III: 2012/2013) of the Resilience for Eating and Activity Despite Inequality study. Primary outcome: BMI based on self-reported height and weight at each wave. Results: There was no evidence of an interaction between time and the number of major chain fast-food outlets within 2 (p=0.88), 3 (p=0.66) or 5 km (p=0.24) in the multilevel models of BMI. Furthermore, there was no evidence of an interaction between time and change in availability at any distance and BMI. Conclusions: Change in BMI was not found to differ by residential major chain fast-food outlet availability among Victorian women residing in disadvantaged neighbourhoods. It may be that exposure to fast-food outlets around other locations regularly visited influence change in BMI. Future research needs to consider what environments are the key sources for accessing and consuming fast food and how these relate to BMI and obesity risk.